Interest in Waqf Among Gen Z: The Role of Technological Literacy and Digital Waqf Innovation - Jalaluddin; Insani, Muhammad Fitrah; Khair Juzaili (Jihbiz: Global Journal of Islamic Banking and Finance, 2026)
The development of digital technology in the modern era has brought significant changes to various aspects of life, including in the field of Islamic philanthropy such as waqf. Generation Z, as the digital generation, has great potential to drive the development of waqf, particularly through the utilization of technology and digital innovation. This study aims to investigate the influence of Technology Literacy and Digital Waqf Innovation on the Interest in Waqf among Generation Z. The study employs a quantitative approach using multiple linear regression analysis and classical assumption tests, conducted on 100 student respondents. Primary data was collected through an online questionnaire. The results indicate that both Technology Literacy and Digital Waqf Innovation have a positive and significant influence on Interest in Waqf, both partially and simultaneously. The coefficient of determination (Adjusted R Square) value of 58.3% indicates that both independent variables contribute strongly to the dependent variable, while the remainder is influenced by other factors not examined in this study. These findings suggest that enhancing understanding of technology and innovation in the management of digital endowments can stimulate interest in endowments among Generation Z.